Annulment of Marriage Due to Husband's Sexual Disorder (Study of Yogyakarta Religious Court Decision Number: 176/Pdt.G/2019/PA. Yk) - Aziz, Satmi Utari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The annulment of marriage is carried out on the grounds that the marriage that has been carried out does not meet the requirements for marriage as described in Law No. 1 of 1974 and the Compilation of Islamic Law for Muslims. However, in the Yogyakarta Religious Court, there is an interesting phenomenon regarding the decision to annul marriage number: 176 / Pdt.G / 2019 / PA. Yk where the request for annulment of marriage was granted. The reason for the annulment of marriage in this case is that the husband suffers from a sexual disorder so the applicant feels cheated. This paper discusses the analysis of why sexual disorders can be used as a reason for annulling marriage as well as a review of Islamic law regarding the legal basis used by the Panel of Judges using the normative juridical approach method. Based on the results of the research and analysis conducted, it was concluded that the sexual disorder submitted by the applicant in the marriage annulment case number: 176/Pdt.G/2019/PA. Yk can be accepted as a form of fraud or misconception committed by the respondent to the applicant. The legal basis used by the Panel of Judges in deciding the marriage annulment case is Article 72 paragraph (2) of the Compilation of Islamic Law, Explanation of Article 72 paragraph (2) of the Compilation of Islamic Law, Arrangements in Article 1328 of the Civil Code, Identity according to Erikson, and based on the Shar'i Proposition in the Book of Sirajul Wahhaj. The review of Islamic law regarding the legal basis used by the panel of judges in deciding this case according to researchers is in accordance with Islamic law